Hoodoo - Fleener, Mary 1951- (3-D Zone, 1988)
Hoodoo is a collection of comics adapted from Barnard alumna Zora Neale Hurston's play Mule Bone. The artist keeps a website of her work at http://www.maryfleener.com
Keywords: Wodu; Comic